Hemodynamic Stability During Severe Scoliosis Surgery Using A Dexmedetomidine-Based Anesthesia Regimen: A Case Report - William Wilson Wantania; Diana Christine Lalenoh (CV. Publikasi Indonesia, 2026)
Severe adult idiopathic scoliosis with a Cobb angle >80° is a complex condition that presents significant anesthetic challenges due to restrictive ventilatory impairment, potential hemodynamic instability, and the risk of massive blood loss during spinal surgery. A 20-year-old woman with an American Society of Anesthesiologists (ASA) Physical Status Classification II was diagnosed with Lenke type 3 idiopathic scoliosis (Cobb angle: 83°) and scheduled for spinal stabilization surgery. Preoperative evaluation revealed a Mallampati class II airway, preserved cardiac function (ejection fraction [EF] 62%), and restrictive pulmonary impairment with low cardiopulmonary risk. General anesthesia was administered using a combination of dexmedetomidine (0.3 mcg/kg/hour), fentanyl (3 mcg/kg), propofol (2 mg/kg), rocuronium (1 mg/kg), and desflurane (6–7 vol%). Intraoperative hemodynamic parameters remained stable. Postoperatively, the patient was successfully extubated in the operating room and transferred to the inpatient ward after 24 hours of intensive care unit (ICU) monitoring, with adequate pain control and no neurological complications. The dexmedetomidine-based anesthesia regimen provided hemodynamic stability, reduced the requirement for additional anesthetic agents, and supported early extubation without respiratory depression. A comprehensive anesthetic approach and blood conservation strategy contributed to optimal clinical outcomes. Comprehensive anesthesia management in severe scoliosis may improve physiological stability, reduce complications, and facilitate recovery.